(untitled) (The New Uzbekistan Journal of Medicine, 2025)
Air pollution poses a critical threat to both human health and the global climate. This article explores the multifaceted impact of airborne pollutants—ranging from particulate matter (PM2.5 and PM10) and nitrogen dioxide (NO₂) to greenhouse gases like carbon dioxide (CO₂) and methane (CH₄). These pollutants are linked to a rise in respiratory diseases, cardiovascular conditions, and premature deaths. At the same time, their accumulation in the atmosphere exacerbates global warming, disrupts weather patterns, and accelerates climate change. The article also highlights the socio-economic disparities in exposure to pollution and emphasizes the urgent need for integrated policy measures, technological innovations, and international cooperation to mitigate these dual threats. Through a comprehensive review of scientific findings, the article aims to raise awareness and foster informed actions toward a cleaner, healthier, and more sustainable future.